Puccini's Tosca - Illica, Luigi, 1857-1919 (Opera Journeys, 2002)
Puccini's Tosca is a high-voltage, powerful and sensational opera thriller that is crammed with actoin, intense, and sometimes ferocious, supercharged dramatic confrontations: a true music drama.
Keywords: Puccini, Giacomo, -- 1858-1924. -- Tosca.; Tosca (Puccini, Giacomo); Operas -- Librettos.; Opéras -- Livrets.; MUSIC -- Genres & Styles -- Opera.; Operas -- Librettos